2020
DOI: 10.1016/j.nicl.2020.102378
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer MEG functional connectivity as a potential marker for suicidal thoughts in major depressive disorder

Abstract: Highlights Generalized slowing of connectivity was seen in those with MDD vs healthy subjects. Slowing from alpha/beta-mediated to delta/theta-mediated connectivity was observed. Connectivity strength and suicidal thoughts were linked in MDD subjects. “Hub” regions in the brain potentially underlying suicidal thoughts were identified. Connectivity differed between those with high suicidal thought scores and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
1
10
1
Order By: Relevance
“…Another study of recent attempters found that suicidal behavior was associated with distinct patterns of connectivity within the executive control network and between the executive control, salience, and default mode networks ( 68 ). Similar findings of distinct, between-network associations between cross-frequency amplitude-amplitude connectivity in low-frequency (delta and theta) bands and SI have been reported, with particular hubs emerging from the hippocampus, anterior insula, and bilateral dorsolateral prefrontal cortex ( 81 ). Furthermore, among young adults diagnosed with MDD, altered connectivity was reported within subregions of the anterior cingulate cortex in suicide attempters compared to non-attempters ( 74 ).…”
Section: Neurobiological Markers Of Suicidal Thoughts and Suicide Rissupporting
confidence: 75%
“…Another study of recent attempters found that suicidal behavior was associated with distinct patterns of connectivity within the executive control network and between the executive control, salience, and default mode networks ( 68 ). Similar findings of distinct, between-network associations between cross-frequency amplitude-amplitude connectivity in low-frequency (delta and theta) bands and SI have been reported, with particular hubs emerging from the hippocampus, anterior insula, and bilateral dorsolateral prefrontal cortex ( 81 ). Furthermore, among young adults diagnosed with MDD, altered connectivity was reported within subregions of the anterior cingulate cortex in suicide attempters compared to non-attempters ( 74 ).…”
Section: Neurobiological Markers Of Suicidal Thoughts and Suicide Rissupporting
confidence: 75%
“…Additional analyses also revealed decreased nodal clustering in several cortical hubs spread over frontal regions, as well as the temporal lobe and the visual cortex [ 157 ]. Multi-layer analyses run on MEG data to explore interareal oscillatory cross-talking showed similar results, namely a decrease in alpha connectivity in depressed participants [ 158 ]. Conversely, alpha-tuned repetitive TMS protocols were shown to ignite an increase in connectivity in MDD, displaying symptom improvements [ 159 ].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…Healthy controls were not included. In the recent MEG study, they didn't capture the group difference, but revealed that electrophysiological connectivity, as coupling of low frequency power (delta and theta) with alpha and beta power, was strongly related to SI [55]. These published MEG study on suicide didn't consider the sub-second dynamics in spontaneous fluctuations, but validated the potential of MEG to explore SA and inspired us to make full use of MEG temporal information.…”
Section: Discussionmentioning
confidence: 99%